Hedinger syndrome: first experience and two-year follow-up in patients with carcinoid heart disease - El Gabry, Mohamed; Shehada, Sharaf-Eldin; Mourad, Fanar; Ruhparwar, Arjang; Lahner, Harald; Dirkmann, Daniel; Thielmann, Matthias; Jakob, Heinz; Wendt, Daniel (Journal of Thoracic Disease, 2019)
Background: Carcinoid heart disease (CHD) (Hedinger syndrome) is a rare manifestation, it has been described in up to 60% of patients with both neuroendocrine tumors (NETs) and carcinoid syndrome (CS) which, typically inducing right heart-sided abnormalities. Methods: Between 07/15 and 10/18, six patients (mean age 63±12 years; 3 females) presented with manifested (NYHA III–IV) Hedinger syndrome’s related valvular(s) lesion and were operated at our center. Clinical data, adverse events and patient outcomes were recorded. Results: The tricuspid valve was involved in all patients. Tricuspid valve repair was possible in four patients and two needed replacement. In two patients, operation was performed on beating heart without cross-clamping. Concomitant pulmonary valve replacement in two patients and aortic valve replacement in another two patients. A mean cross-clamp time of 61±50 minutes was observed. One patient with severely impaired right ventricular function needed ECMO support, and died 3 days later due to neuroendocrine enzyme storm. At 13 months, one patient developed severe tricuspid stenosis and underwent re-operation with replacement. Another patient died 18 months after surgery related to the underlying tumour. At mean of 30 months follow-up, four patients were alive and asymptotic. Conclusions: Hedinger syndrome is a challenging entity in cardiac surgery characterized by aggressive valve lesions combined with metastatic neuroendocrine neoplasia affecting the systemic circulation. We advise a multidisciplinary collaboration to early diagnose cardiac involvement to offer an early and proper treatment regime.